International Jurisdiction over Standard-Essential Patents - Henrik Horn (Research Institute of Industrial Economics (IFN), 2020)
A sizeable literature analyzes the appropriate interpretation of FRAND commitments for standard-essential patents. With few exceptions, the literature disregards international dimensions, despite the fact that most standards are used in international markets. This paper uses a simple economic setting to assess pros and cons of the main jurisdictional bases in international law—the Territoriality and Nationality Principles—when national regulatory authorities have conflicting views regarding the appropriate interpretation of FRAND commitments. The paper identifies situations where the bases can implement efficient outcomes, and where they fail. The paper also shows how non-discrimination obligations might improve upon the outcomes.
Keywords: F15; K21; K33; L40; O38; 330; Standard-essential patents; International jurisdiction; Default rules